In the rainforest - Taylor, Barbara, 1954- (Hauppauge, N.Y. : Barron's Educational Series, 1999)
Color photographs and text provide information about the various plants and animals that live in the world's rainforests.
Includes index.
4.7
3-6
Keywords: Rain forest animals -- Juvenile literature; Rain forest ecology -- Juvenile literature; Rain forest plants -- Juvenile literature; Rain forests -- Juvenile literature; Rain forest animals; Rain forest ecology; Rain forest plants; Rain forests; Rain forest animals; Rain forest plants